PREPARASI DISPERSI ANTIBAKTERI BERBAHAN DASAR TITANIUM DIOKSIDA (TIO2) SERTA APLIKASINYA PADA KAIN DENGAN METODA DIP COATING - Bunga Fisikanta Bukit; Syarif Hussein Sirait (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
Cases of nosocomial infections in Indonesia are increasing every year. One of the reasons is hospital equipment that is not sterile and poorly maintained in public facilities used in hospitals such as sheets, pillowcases, blankets, curtains, towels, and patient clothes. Everything made from fabrics can be contaminated by bacteria causing infections. In this research, the preparation of antibacterial based on titanium dioxide (TiO2) and its application to the fabric using a simple methodology. Cross-linking using Maleic Acid and catalyst using sodium hypophosphite. The dip-coating method is used to coat the fabric. Then, fabric washing is carried out to see the decrease in the amount of TiO2. Plate Count Method is carried out to see the antibacterial activity on the fabric. Fabric characterization was carried out using SEM and FTIR. SEM shows that TiO2 particles distributed throughout the fabric surface. After washing 10 times, there is a reduction in the amount of TiO2 in the fabric. FTIR aims at cross-linking between TiO2 and fabric. Meanwhile, testing for antibacterial activity showed that no bacteria appeared in all samples.